Studi Kelayakan Usaha Infused Water Untuk Kesehatan Gigi dan Mulut - Sukmawati, Dalfa Destiana; Heriyanto, Yonan; Deru Marah Laut; Yenni Hendriani Praptiwi (Poltekkes Kemenkes Bandung, 2024)
A feasibility study is an action that involves in-depth research on a venture or business that will be implemented, with the aim of assessing whether the business is suitable to be run or not. Red grape infused water has potential in preventing dental caries. This is because red grape infused water can increase the pH level of plaque and saliva, so it can inhibit the growth of plaque bacteria and the production of acid by plaque bacteria. Aims to understand market and marketing aspects, technical and technological aspects, operational management aspects, financial aspects, juridical aspects. This type of research is qualitative. Data collection was carried out using interview and observation techniques. Shows sales of infused water drinks in Cibatu District, products sold at a decent profit. The infused water business is declared feasible from market and marketing aspects, technical and technological aspects, operational management aspects, financial aspects and juridical aspects. Apart from that, infused water can be used as an entrepreneurial activity in your free time.